FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELENGKAPAN IMUNISASI DASAR BAYI - Sriyanah, Nour; Achmad, Ismiyanti H.; Anwar, Yulianti; Hutabarat, Naomi Isabella (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Basic immunization is a strategic step in preventing polio, diarrhea, congenital defects, and delays in physical and cognitive development. Tomuan Health Center is one of the health centers in Pematang Siantar City with low immunization achievements. The purpose of the study was to determine the factors associated with the completeness of basic immunization of infants. The research design used in this study was cross sectional. The research was conducted in the Tomuan Health Center working area. The research was conducted in October 2023. The study population was all mothers who have babies who have reached the age of 12 months who live around the Tomuan Health Center working area. The research sample amounted to 50 respondents who were selected using simple random sampling. The research instrument used a research questionnaire. Data analysis was conducted univariate and bivariate. The results showed family support (p value: 0.001), maternal confidence (p value: 0.001) on the provision of complete basic immunization. It is recommended that the puskesmas provide information in counseling and increase the motivation of mothers regarding the importance of immunization and monitor the completeness of immunization so as to create trust in doing this and for mothers who have infants and toddlers should be more active in seeking information about basic immunizations that should be given to children because this is very influential with the mother's knowledge.Keywords: Toddlers, Family Support, Basic Immunization.